Pengaruh Pembelajaran Berdiferensiasi terhadap Peningkatan Hasil Belajar Pendidikan Agama Katolik dan Budi Pekerti Kelas X di SMK Sanjaya Pakem - Alexander Hendra Dwi Asmara; Maria Anuntiata (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2025)
This research applies a quantitative approach by applying one group pretest-posttest. To collect samples, researcher used a saturated sampling technique. Then, 50 people were selected as the sample. Learning outcome tests are used to collect research data. Later, data were deeply examined using the normality test, hypothesis testing, followed by simpel linear regression test. The study findings indicate that the average pretest score is 72.73 and the posttest score is 88.75, as evidenced by the pretest and post learning outcomes data. The average value indicates a notable variance in values pre and post treatment. This indicates that Ha has been approved. This indicates that the pretest and posttest scores differ, revealing that differentiated learning strategies have increased learning achievements of Catholic religious education in class X SMK Sanjaya Pakem. Furthermore, according to a basic linear regression analysis, it was determined that personalized instruction had a significant impact of 72.4%. The researcher recommended that Catholic religious education teachers utilize differentiated learning strategies to enhance student learning results in Catholic religious subjects.